2012
DOI: 10.1186/1471-2466-12-30
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory tract mortality in cement workers: a proportionate mortality study

Abstract: BackgroundThe evidence regarding the association between lung cancer and occupational exposure to cement is controversial. This study investigated causes of deaths from cancer of respiratory tract among cement workers.MethodsThe deaths of the Greek Cement Workers Compensation Scheme were analyzed covering the period 1969-1998. All respiratory, lung, laryngeal and urinary bladder cancer proportionate mortality were calculated for cement production, maintenance, and office workers in the cement industry. Mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
1
12
0
1
Order By: Relevance
“…For lung cancer mortality, the pattern of SMRs was similar to that seen for all cancers with four of the seven studies reporting SMRs with CIs overlapping the null, two studies showing slightly decreased SMRs (SMR=0.53, 95% CI 0.27 to 0.95)12 and (SMR=0.56, 95% CI 0.32 to 0.89),6 and one reporting an increase for lung cancer (n=85 cases; PMR=2.05, 95% CI 1.65 to 2.627; figure 2). The meta-SMR for lung cancer mortality was 0.93 (95% CI 0.62 to 1.39).…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…For lung cancer mortality, the pattern of SMRs was similar to that seen for all cancers with four of the seven studies reporting SMRs with CIs overlapping the null, two studies showing slightly decreased SMRs (SMR=0.53, 95% CI 0.27 to 0.95)12 and (SMR=0.56, 95% CI 0.32 to 0.89),6 and one reporting an increase for lung cancer (n=85 cases; PMR=2.05, 95% CI 1.65 to 2.627; figure 2). The meta-SMR for lung cancer mortality was 0.93 (95% CI 0.62 to 1.39).…”
Section: Resultssupporting
confidence: 68%
“…8 10 12 33 The meta-SMR for colon and rectal cancer mortality was 1.05 (95% CI 0.79 to 1.40). Cement work was not associated with significant increases or decreases in pancreas cancer mortality in two studies (SMR=1.01, 95% CI 0.43 to 1.98) and (SMR=0.80, 95% CI 0.36 to 1.60)8 12 or with bladder cancer mortality in two studies (SMR=1.10, 95% CI 0.44 to 2.43) and (PMR=1.52, 95% CI 0.85 to 2.55) 7 8…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…The relation between lung cancer and occupational exposure to cement remains inconclusive and controversial where other studies showed negative relationship. 35 Moreover, this study revealed that 16.3% of cases were farmers (Table 1); of them 34.4% had LCC, 15.4% had SCC and 7.9% had ADC (Table 4). This finding might be possibly point out the relation between farming environment and an increased risk of bronchogenic carcinoma.…”
Section: Occupational Risk Factorsmentioning
confidence: 73%